Rapid eye movement-sleep is reduced in patients with acute uncomplicated diverticulitis—an observational study - Chenxi Huang; Mahdi Alamili; Claus Henrik Nielsen; Jacob Rosenberg; Ismail Gögenur (PeerJ, 2015)
Introduction. Sleep disturbances are commonly found in patients in the postoperative period. Sleep disturbances may give rise to several complications including cardiopulmonary instability, transient cognitive dysfunction and prolonged convalescence. Many factors including host inflammatory responses are believed to cause postoperative sleep disturbances, as inflammatory responses can alter sleep architecture through cytokine-brain interactions. Our aim was to investigate alteration of sleep architecture during acute infection and its relationships to inflammation and clinical symptoms.Materials & Methods. In this observational study, we included patients with acute uncomplicated diverticulitis as a model to investigate the isolated effects of inflammatory responses on sleep. Eleven patients completed the study. Patients were admitted and treated with antibiotics for two nights, during which study endpoints were measured by polysomnography recordings, self-reported discomfort scores and blood samples of cytokines. One month later, the patients, who now were in complete remission, were readmitted and the endpoints were re-measured (the baseline values).Results. Total sleep time was reduced 4% and 7% the first (p = 0.006) and second (p = 0.014) nights of diverticulitis, compared to baseline, respectively. The rapid eye movement sleep was reduced 33% the first night (p = 0.016), compared to baseline. Moreover, plasma IL-6 levels were correlated to non-rapid eye movement sleep, rapid eye movement sleep and fatigue.Conclusion. Total sleep time and rapid eye movement sleep were reduced during nights with active diverticulitis and correlated with markers of inflammation.